Is digital finance always beneficial to accounting information transparency? Evidence from China - Xingqiang Du; Jing Hong; Hexin Tao; Yongkui Zhang (China Journal of Accounting Studies (CJAS), 2024)
Using a sample of Chinese listed firms over 2011-2020, this study examines the impact of digital finance on accounting information transparency. Our findings reveal an inverted U-shaped relationship between digital finance and accounting information transparency, suggesting that digital finance within certain limits increases accounting information transparency by optimising information acquisition and processing, but excessive digital finance leads to information overload and impairs accounting information transparency. Our findings are robust to a variety of sensitivity tests and are still valid after using two-stage "shift-share" instrumental variable procedures, propensity score matching method and firm-level fixed effect regression to control for the endogeneity issue. Lastly, MD&A and annual reporting disclosure timeliness are two influential channels by which digital finance affects accounting information transparency, and further the inverted U-shaped relationship is more pronounced for firms in provinces with lower marketisation indexes (CEO-chairman duality) than for their counterparts.
Keywords: 650; accounting information transparency; Digital finance; information overload; the inverted U-shaped relationship